Migrant Health in Cancer: Outcome Disparities and the Determinant Role of Migrant‐Specific Variables. (23rd March 2015) - Sze, Ming; Butow, Phyllis; Bell, Melanie; Vaccaro, Lisa; Dong, Skye; Eisenbruch, Maurice; Jefford, Michael; Girgis, Afaf; King, Madeleine; McGrane, Joshua; Ng, Weng; Asghari, Ray; et al.
Abstract : Background: Multiethnic societies face challenges in delivering evidence‐based culturally competent health care. This study compared health‐related quality of life and psychological morbidity in a hospital‐based sample of first‐generation migrants and Australian‐born Anglo cancer patients, controlling for potential confounders related to migrant status. Further, it explored the relative contribution of ethnicity versus migrant‐related variables. Methods: Eligible participants, recruited via 16 oncology clinics in Australia, included those over the age of 18, diagnosed with cancer (any type or stage) within the previous 12 months and having commenced treatment at least 1 month previously. Results: In total, 571 migrant patients (comprising 145 Arabic, 248 Chinese, and 178 Greek) and a control group of 274 Anglo‐Australian patients participated. In multiple linear regression models adjusted for age, sex, education, marital status, socioeconomic status, time since diagnosis, and type of cancer, migrants had clinically significantly worse health‐related quality of life (HRQL; 3.6–7.3 points on FACT‐G, p < .0001), higher depression and anxiety (both p < .0001), and higher incidence of clinical depression ( p < .0001) and anxiety ( p = .003) than Anglo‐Australians. Understanding the health system ( p < .0001 for each outcome) and difficulty communicating with the doctor ( p = .04 to .0001) partially mediated the impact of migrancy. In migrant‐only analyses, migrant‐related variables (language difficulty and poor understanding of the health system), not ethnicity, predicted outcomes. Conclusion: Migrants who develop cancer have worse psychological and HRQL outcomes than Anglo‐Australians. Potential targets for intervention include assistance in navigating the health system, translated information, and cultural competency training for health professionals. Abstract : This study compared health‐related quality of life and psychological morbidity in a hospital‐based sample of first‐generation migrants and Australian‐born Anglo cancer patients and explored the relative contribution of ethnicity versus migrant‐related variables. In multiple linear regression models adjusted for age, sex, education, marital status, socioeconomic status, time since diagnosis, and type of cancer, migrants who develop cancer have worse psychological and health‐related quality of life outcomes than Anglo‐Australians.